Jedermann de Hugo von Hofmannsthal et de Felix Mitterer - Diane de Wrangel (Recherches Germaniques)
As we have just celebrated the centenary of the Salzburg Festival in 2020, Hugo von Hofmannsthal’s well-known play, Jedermann—traditionally performed every year at the opening of the festival—continues to be a great success with today’s audiences. This theatrical work is based on an English morality dating back to the end of the 15th century, and it features allegorical characters as if in a Dance of Death. It contains a timeless principle that provides the basis for rewritings, as Ein Jedermann (1991) by Austrian playwright Felix Mitterer shows. As morality plays, both works have the same didactic purpose, which is to help the audience to better understand the meaning of existence and the human condition. Each in its own way, these plays enter into dialogue with the society of their time by re-actualising the aesthetic forms of the past.